Testing of core-based systems-on-a-chip. - Ravi, S. (IEEE Transactions on computer-aided design of integrated circuits and systems)
Available techniques for testing of core-based systems-on-a-chip (SOCs) do not provide a systematic means for synthesizing low-overhead test architectures and compact test solutions. In this paper, we provide a comprehensive framework that generates low-overhead compact test solutions for SOCs. First, we develop a common ground for addressing issues such as core test requirements, core access, and testing hardware additions. For this purpose, we introduce finite-state automata (FSA) for modeling tests, transparency modes, and testing hardware behavior. In many cases, the tests repeat a basic set of test actions for different test data that can again be modeled using FSA. While earlier work can derive a single symbolic test for a module in a register-transfer level (RTL) circuit as a finite-state automaton, this work extends the methodology to the system level and additionally contributes a satisfiability-based solution to the problem of applying a sequence of tests phased in time. This problem is known to be a bottleneck in testability analysis not only at the system level, but also at the RTL. Experimental results show that the system-level average area overhead for making SOCs testable with our method is only 4.5%, while achieving an average test application time reduction of 80% over recent approaches. At the same time, it provides 100% test coverage of the precomputed test sets/sequences of the embedded cores